Uma análise pragmática do controle da atividade jurisdicional nos juizados especiais: as inconsequências práticas da tomada de decisão vinculante no que concerne às taxas incidentes em contratos bancários - Porto, Giovanni Magalhaes (2014)
From the great legitimation system conquered by the special civil courts system for consumers (small-claims courts), to allow, independent of the intermediation of the attorney or of the the preparation of legal costs, a bigger effectiveness of the access to justice in demands proposed in relation to to organizational litigants, will be analyzed in this study, specifically, in relation to claims for repetition rates like TAC/TEC and resembled in vehicle financing contracts, the legitimacy and effectiveness of the interference of judicial activity, assigned to Superior Court STJ in place of complaints and special features, from the creation of normative control erga omnes, contained in the precedent of the RE 571.572ED, from the the Supreme Court - STF, and the difficulties raised from the practical inconsequences of such decision in relation to the system of courts, constitutionally established without ordinary control of that Superior Court of Justice. It is that the novel binding of judges to the superior courts of law does not fit the peculiar principle of sociability matter of law contained in the art.6º, of the Law No. 9099/95, which states that the magistrate adopts, in each case, the "decision considered fair and equitable, addressing the social purposes of the law and the requirements of the common good", and which criteria privilege the construction of the ratio decidendi less exegetical, that can be better understood with the use of the method abduction of Charles Sanders Peirce, in a context of discovery in which the preconceptions of the applicator would indicate what would be more believable in law debate, reflecting on the fact put in order to build, in the context of justification of the rhetoric of judicial entimema, its understanding. To this end the suspension of proceedings determined by Exma. Ministra Isabel Gallotti will be examined, in the records of REsp 1.251.331-RS, who answered a request from FEBRABAN preventing the processing of actions even tried in the first instance as well as the judgment of the Second Section that followed it, that searching for a standardization of judicial understanding, brought serious practical inconsistencies before the theory of law, especially consumerist legislation and procedural logic, regarding a matter that involves more than two hundred and eighty-five thousand lawsuits processes in progress, in which it is discussed the legality of charging of credit facility, issuance docket and resembled in bank financing contracts.